Surgeons opinions of legal practice in bile duct injury following cholecystectomy. Issue 8 (August 2017) - Gordon-Weeks, Alex; Samarendra, Harsh; de Bono, John; Soonawalla, Zahir; Silva, Michael
Abstract: Introduction: Litigation for bile duct injury following laparoscopic cholecystectomy places financial strain on the health service, causes significant patient morbidity and adversely affects the patient and surgeon. Claimants argue that the injury itself is evidence of negligence. Methods: A questionnaire addressing views on BDI causation was sent to members of AUGIS working in the National Health Service, UK. Response themes and responses were compared between groups of surgeons. Results: Of 117 respondents, 45% experienced BDI and 22% had medicolegal experience. 47% of respondents identified factors outside the surgeons control as being relevant to BDI. Those that had experienced BDI from their own surgery were less likely to identify surgeon/systems errors as the primary cause for BDI than those that had not (34% vs 74%, p < 0.001). Medicolegal expert surgeons were more likely to report that substandard technique should be presumed (50% vs 19%, p = 0.002), however, 25% of medicolegal experts indicated that not all BDIs caused by their own surgery could have been avoided. Conclusion: A significant number of experienced surgeons indicated that BDI following LC should not be assumed to result from surgeon negligence or institutional failure. This suggests that negligence should not be inferred from the act of BDI alone.